Pengaruh Perlakuan Imbangan Garam dan Gula Terhadap Kualitas Dendeng Paru-Paru Sapi (Faculty of Animal Science Universitas Brawijaya, 2015)
The aim of this study was to determine the effect of concentration salt and sugar of dried lung quality. The material used in this research was the dried lung with different salt and sugar concentration as the treatments. The method of this research was factorial experiment with Completely Randomized Design by using two factors. The treatments were different salt concentration (2.5% and 5%) with different sugar concentration (20%, 30% and 40%). Data was analyzed with ANNOVA and continued with Duncan’s Multiple Range Test (DMRT). Variables tested were water level, protein content, fat, water activity and pH. The result showed that salt addition gave highly significant effect (P<0.01) on water level but not significant (P>0.05) on protein, fat, water activity and pH. The result showed that sugar addition gave highly significant effect (P<0.01) on water level but not significant (P>0.05) on protein, fat, water activity and pH. The experiment result indicated that the optimum concentration of salt was 2.5% with concentration of sugar 20% to making dried lung.